Investigation of VGLL3 and sub-target genes in the aetiology of paediatric acute appendicitis: a prospective case-control study - Tartar, Tugay; Akdeniz, Ibrahim; Onalan, Ebru; Bakal, Unal; Sarac, Mehmet; Genc, Ercan; Kazez, Ahmet (Springer, 2023)
PurposeVestigial like family member 3 (VGLL3) and its sub-target genes show considerable transcriptomic overlap in terms of several autoimmune and inflammatory diseases. Herein, we investigated the role of VGLL3 rs13074432 polymorphism and its sub-target genes in the aetiology of acute appendicitis (AA).MethodsIn this prospective case-control study, we included 250 patients (age, 0-18 years) who underwent appendectomy with the diagnosis of AA (patient group; blood and appendix tissue samples) and 200 healthy children (control group; only blood samples) without appendectomy. ELISA method was used for protein-level detection of VGLL3 and sub-target genes expression change in obtained tissue samples, and real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used for mRNA level detection. Genotyping analyses were performed on DNA samples isolated from blood using TaqMan SNP genotyping test.ResultsThe frequency of TT variant genotype (p < 0.001) and T allele (p = 0.002) showed a significant decrease in the patient group compared with the control group. No significant correlation was observed between the expression of VGLL3 in the appendiceal tissue and patient clinical and demographic data (p > 0.050).ConclusionThis study revealed that the VGLL3 gene and its sub-target genes are associated with AA aetiology.
38th Annual Meeting of the Turkish Association of Pediatric Surgeons (TAPS) Congress -- NOV 25-28, 2021 -- Antalya, TURKEY
Keywords: Acute appendicitis; Aetiology; Genetics; Children